Intercostal nerve cryoanalgesia in the treatment of pain in patients operated on by the modified Nuss method with the BackOnFeet application—a new strategy to improve outcomes - Zacha, Sławomir; Andrzejewska, Agata; Jastrzębska-Ligocka, Barbara; Szwed, Aleksander; Modrzejewska, Elżbieta; Zacha, Wojciech; Skonieczna-Żydecka, Karolina; Miegoń, Jakub; Jarosz, Konrad; Biernawska, Jowita (Frontiers in Pediatrics, 2023)
Introduction The surgical Nuss correction of the funnel chest deformity is a painful procedure without an established consensus of pain relief methods. High doses and long duration of opioids requirements impedes the ERAS protocol introduction. The aim of this study was to evaluate the effectiveness of intraoperative intercostal nerve cryolysis in terms of pain management in relation to the routinely used multimodal analgesia in Poland. We also assessed the impact of using the proprietary “BackOnFeet” application on the quality of life of patients after surgery in relation to the ERAS protocol. Methods The prospective, single-centre, non-randomised, before—after pilot study was conducted. Inclusion criteria were: funnel-shaped chest deformity, age range 11–18 years, first chest wall operation, agreement for the cryolysis and regional analgesia, no history of chronic painkillers use. The results of the “control group” (multimodal analgesia with regional analgesia commonly performed in Poland) were assessed. The interdisciplinary perioperative protocol with the “BackOnFeet” application and intraoperative intercostal nerve cryoanalgesia were introduced to the “intervention group”. Results Eighteen children were treated with standard protocol typical for Polish management and matched to eighteen patients who received cryoanalgesia and the “BackOnFeet” application access “intervention group”. We noticed lower NRS points in first 24 h (p = 0.0048), shortening of time of opioid use (p = 0.0002), hospitalisation time (p = 0,01), improved quality of postoperative rehabilitation (p < 0.0001) and quality of life (p < 0.0001) among the “intervention group”. Conclusions Intraoperative intercostal nerves cryolysis performed during the minimally invasive Nuss correction of funnel deformation in combination with bilateral is more effective in terms of acute pain management in relation to the routinely used multimodal analgesia in Poland, allowing for the shortening of time of opioid use, hospitalisation time, improved quality of postoperative rehabilitation and enabled ERAS protocol introduction. The use of the proprietary “BackOnFeet” application has a positive effect on the quality of life of patients after surgery.